2022
DOI: 10.1126/sciadv.abj6526
|View full text |Cite
|
Sign up to set email alerts
|

HSF2 cooperates with HSF1 to drive a transcriptional program critical for the malignant state

Abstract: Heat shock factor 1 (HSF1) is well known for its role in the heat shock response (HSR), where it drives a transcriptional program comprising heat shock protein (HSP) genes, and in tumorigenesis, where it drives a program comprising HSPs and many noncanonical target genes that support malignancy. Here, we find that HSF2, an HSF1 paralog with no substantial role in the HSR, physically and functionally interacts with HSF1 across diverse types of cancer. HSF1 and HSF2 have notably similar chromatin occupancy and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 78 publications
3
22
0
Order By: Relevance
“…Despite the minor effect of HSF2 on stress-induced transcription, HSF2 was found to co-localize to the same sites as HSF1 during both oxidative stress and heat shock, indicating that HSF2 cooperates with HSF1 to orchestrate transcription in response to different types of stress (Figure 3A – C ). This is in line with a recent finding demonstrating that HSF2 occupies the same target genes with HSF1 in cancer to drive malignancy ( 18 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the minor effect of HSF2 on stress-induced transcription, HSF2 was found to co-localize to the same sites as HSF1 during both oxidative stress and heat shock, indicating that HSF2 cooperates with HSF1 to orchestrate transcription in response to different types of stress (Figure 3A – C ). This is in line with a recent finding demonstrating that HSF2 occupies the same target genes with HSF1 in cancer to drive malignancy ( 18 ).…”
Section: Resultssupporting
confidence: 92%
“…Intriguingly, exogenous human HSF2, but not HSF1, can substitute for yeast HSF to provide thermotolerance, demonstrating that HSF2 has a capability to act as a stress-responsive transcription factor ( 16 ). There is also evidence for a context-dependent interplay between HSF1 and HSF2, either competitive or synergistic, but the functional role of HSF2 in stress-inducible transcription has remained elusive ( 17 , 18 ). Although HSF1 has been identified as the master regulator of the heat shock response and other proteotoxic stresses, it is also activated in response to oxidative stress ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…We note that RPRD1B function in the HS response is unlikely to be due to a direct interaction with HSF1. Indeed, several proteomic studies have established the HSF1 interactome, and RPRD1B was not identified as a partner in these experiments ( Burchfiel et al, 2021 ; Smith et al, 2022 ; Takii et al, 2019 ; Zhang et al, 2019 ). Furthermore, HSF1 appears to be normally activated in cells depleted for RPRD1B.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, libraries were constructed with the Illumina TruSeq Stranded mRNA Library Preparation Kit and sequenced on an Illumina NextSeq 500 at the Northwestern University, NUSeq core facility. DNA read quality control and RNA-Seq analysis was performed as described previously 75 with the following modifications. The quality of DNA reads, in fastq format, was evaluated using FastQC.…”
Section: Methodsmentioning
confidence: 99%